MODERN RISK FORECASTING MODELS IN THE COMPANY - Satymbekova Katira,; Nurmaganbetova Begzat ,; Makenova Ajgul,; Basshieva Zhangul, (Academic Journal of Physical and Chemical Sciences, 2020)
Companies independently develop and form their financial relations, financial resources, determine the direction of their use and effectively organize financial management, consider ways to improve the company's competitiveness in the conditions of market globalization. Financial management of a company determines the coordination of all activities of an economic entity, since financial relations, financial resources and sources of financial resources that are its object determine not only current, but also stable competitiveness in a market economy. In modern conditions, when companies with their own needs make financial decisions, its resource capabilities increase dramatically. This means optimizing financial relations and improving the efficiency of financial resource management. Indicators of financial condition reflect the profitability of economic activities, financial achievements and competitiveness. The information system satisfies the interest not only of the business entity to the owners and management personnel, but also to a wide range of its external users with the necessary information. Risk management in any company is defined separately depending on the volume of construction work and the amount of financial resources. The implementation of these measures will help to reduce the amount of unexpected losses from exposure to risks. The actual performance of the functions of the enterprise's financial management system allows the company's management to control financial and economic activities in financial management and correct the directions of inefficiently performed activities. Because improving competitiveness is the result of effective financial management policies and functions. Thus, financial management will increase the role of the financial Manager in the effective management of the company's finances, regulation of financial relations and search for effective sources of financing, increasing the profitability of financial and economic activities, and cash flows.